2007
DOI: 10.1097/brs.0b013e31814b1c0b
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Development of Delayed Infections Following Posterior Spinal Fusion and Instrumentation in Adolescent Idiopathic Scoliosis Patients

Abstract: The occurrence of a delayed infection is most likely multifactorial and is related to a positive past medical history and the use of blood transfusions. Postoperative use of a drain may be important to avoid delayed infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(88 citation statements)
references
References 29 publications
4
80
1
3
Order By: Relevance
“…Ho et al reviewed 36 patients with delayed infections in adolescent idiopathic scoliosis who underwent posterior spinal fusion and found that the incidence of delayed infections was directly related to the blood transfusion. 10 Christodoulou et al found that high allogenic blood transfusion rates were significantly associated with increased acute infection in adult spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ho et al reviewed 36 patients with delayed infections in adolescent idiopathic scoliosis who underwent posterior spinal fusion and found that the incidence of delayed infections was directly related to the blood transfusion. 10 Christodoulou et al found that high allogenic blood transfusion rates were significantly associated with increased acute infection in adult spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…10,23 Clinical experiences suggest that surgical time, longer fusion segments of the spine, not using postoperative drains, and increased drainage when drains are used may also correlate with delayed infection. In this retrospective, nonrandomized study we analyzed the predictors of delayed infections after spinal fusion and instrumentation in patients with scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Rihn et al [30] reviewed 236 adolescent patients who underwent spinal surgery for adolescent idiopathic scoliosis to identify specific risk factors for SSI and found 7 (3%) cases of SSI and described the treatment of these infections but did not identify any specific risk factors for developing SSI. Ho et al [31] also reviewed adolescent idiopathic scoliosis patients and identified ''significant medical history'', receipt of blood transfusions and failure to use a postoperative drain as factors that increased risk of SSI but was limited by its population size. Other small studies in the literature have not been able to identify patient or surgical characteristics resulting in significantly increased risk for SSI [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Closed-suction drains are used frequently in the setting of spinal surgery, as they are believed to reduce the incidence of post-operative hematoma, compression of the cauda equina, and resultant neurological defects [80][81][82]. The correlation between CSD and SSI has been examined in this literature, albeit with conflicting results.…”
Section: Spine Surgerymentioning
confidence: 99%
“…Ho et al [82] performed a retrospective case-control study in which adolescent patients with idiopathic scoliosis who underwent posterior spinal fusion and instrumentation (PSFI) and developed a ''delayed'' SSI (n = 36) were matched with randomly selected non-infected controls (n = 90). All patients received antibiotic prophylaxis, but neither the timing nor the duration was associated with the development of delayed SSI.…”
Section: Spine Surgerymentioning
confidence: 99%